Occupational stress in elementary school faculty members in Rio Grande do Sul: A gender analysis - Marcus Levi Lopes Barbosa; Denise Regina Quaresma da Silva; Lisiane Machado de Oliveira Menegotto; Ronei Saldanha Lopes (Arizona State University, 2017)
This study examines the occupational stress levels of elementary school teachers in the Municipal Education System of a city in the Vale dos Sinos (Rio Grande do Sul, Brazil), and verifies its occurrence by gender, as well as by age and teaching work time. This quantitative, cross-sectional study evaluates the presence of stress on 50 adults through the LIPP - ISSL Inventory of Stress Symptoms for Adults (Lipp, 2000). The results show that the women in the study experienced more physical symptoms of stress than the evaluated men did. It also indicates that stress maybe a characteristic of the teaching activity, since it affects both younger and older faculty members, as well as professors at the beginning, middle and end of their careers.